Changes in exertion-related symptoms in adults and youth who have sustained a sport-related concussion. Issue 1 (January 2021) - Rutschmann, Trevor D.; Miutz, Lauren N.; Toomey, Clodagh M.; Yeates, Keith O.; Emery, Carolyn A.; Schneider, Kathryn J.
Abstract: Objectives: To identify the symptoms responsible for cessation of exercise testing and evaluate changes in post-concussion symptom scores on the Post-Concussion Symptom Scale (PCSS) from the Sport-Concussion Assessment Tool (SCAT5) immediately, 1–4 h, and 6–12 h following completion of the Buffalo Concussion Treadmill Test (BCTT) in youth and adults who have sustained a sport-related concussion. Design: Prospective case-series. Methods: Individuals who were diagnosed with a sport-related concussion and self-reported difficulties with exertion were referred to perform an exertional treadmill test. Individuals were recruited from a university sports medicine clinic. Change in PCSS symptom severity scores were operationally defined as a change ≥4 points. Results: Forty-five individuals aged 13–57 years consented to participate. A total of 14/24 (58.3%) female and 13/21 (61.9%) male participants reported an increase in symptom severity scores immediately following the BCTT. At 1–4 h, 5/10 (50.0%) males and 5/14 (35.7%) females who completed the PCSS had elevated symptom severity scores compared to pre-exertion. Only 24.2% (3/17 males and 5/16 females) of participants completing the PCSS at 6–12 h reported increased symptom severity scores. Conclusion: Exertional testing is an important component of a multifaceted assessment following concussion; however, previous research evaluating symptom responses to exertion is limited. This study provides evidence to suggest individuals who experience an exacerbation of concussion-associated symptoms after exertion are likely to return to pre-exertion levels within the same day. Future research monitoring symptoms following exertion and throughout recovery should be performed in tandem with physiological measures to better understand the source of symptoms.